O20.4 Transmission risk beliefs influence sexual risk behaviour of hiv-positive msm. (13th September 2015) - Truong, HM; Fatch, R; Nguyen, B; Grasso, M; Robertson, T; Raymond, HF; McFarland, W
Abstract : Introduction: Beliefs about the efficacy of antiretroviral treatment for decreasing risk of HIV transmission may influence a person's sexual risk behaviour. We examined whether individuals' HIV transmission risk beliefs predicted subsequent engagement in unprotected anal intercourse (UAI) among men who have sex with men (MSM). Methods: HIV-positive and HIV-negative MSM were recruited for the longitudinal study in San Francisco using time-location sampling. Participants who completed both the baseline and  6-month follow-up behavioural surveys were included in the analysis (N = 773). Beliefs regarding HIV transmission risk at baseline and reported UAI with any sexual partner during the 6-month interval between the baseline and follow-up surveys were evaluated. Results: UAI at baseline was associated with an increased likelihood of UAI at follow-up among both HIV-positive MSM (OR = 6.45, p < 0.01) and HIV-negative MSM (OR = 13.59, p < 0.01). UAI was more frequently reported at follow-up among HIV-positive MSM who agreed with the statements, "Because of combination drug treatment for HIV, I am less concerned about infecting someone, " (OR = 2.49, p = 0.04) and "I am less worried about having UAI now that treatments can be taken after unprotected sex, " (OR = 6.52, p = 0.02). HIV-positive MSM who agreed with statement, "My sexual practices are safer because someone who is positive can become re-infected with HIV, " were less likely to report UAI at follow-up (OR = 0.13, p < 0.01). Transmission risk beliefs were not associated with UAI at follow-up among HIV-negative MSM. Conclusion: HIV-positive MSM who believed there was less risk of transmitting HIV due to the availability of antiretroviral treatment and post-exposure prophylaxis were more likely to engage in UAI. Concerns about the possibility of re-infection may have influenced some HIV-positive men to refrain from engaging in UAI. These findings suggest the need for prevention messages to highlight treatment adherence and viral suppression as important factors that affect the efficacy of antiretrovirals for reducing HIV transmission risk. Disclosure of interest statement: This work was supported by the US National Institutes of Health [R01 MH077509].